Violence against women: criminological perspectives on men's violences - Westmarland, Nicole (Routledge, 2015)
Fatal violence against women : partner homicide -- Physical partner violence -- Intimate partner sexual violence -- Psychological abuse -- Violence against mothers and grandmothers -- Forced marriage -- Honour based violence and killings -- Female genital mutilation -- Familial rape and abuse -- Sexual violence and harassment in the work place -- Street and public space violence -- Stranger and acquaintance rape -- Sexual violence, celebrity culture, and public institutions -- Institutional abuse in residential care -- Violence against women in higher education institutions